Astrocytic and neuronal accumulation of elevated extracellular K+ with a 2/3 K+/Na+ flux ratio—consequences for energy metabolism, osmolarity and higher brain function - Hertz, Leif; Xu, Junnan; Song, Dan; Yan, Enzhi; Gu, Li; Peng, Liang (Frontiers in Computational Neuroscience, 2013)
Brain excitation increases neuronal Na+ concentration by 2 major mechanisms: i) Na+ influx caused by glutamatergic synaptic activity; and ii) action-potential-mediated depolarization by Na+ influx followed by repolarizating K+ efflux, increasing extracellular K+ concentration. This review deals mainly with the latter and it concludes that clearance of extracellular K+ is initially mainly effectuated by Na+,K+-ATPasemediatedK+ uptake into astrocytes, at K+ concentrations above ~10 mM aided by uptakeof Na+, K+ and 2 Cl- by the cotransporter NKCC1. Since operation of the astrocytic Na+,K+-ATPase requires K+-dependent glycogenolysis for stimulation of the intracellular ATPase site, it ceases after normalization of extracellular K+ concentration. This allows K+ release via the inward rectifying K+ channel Kir1.4, perhaps after trans-astrocytic connexin- and/or pannexin-mediated K+ transfer, which would be a key candidate for determination by synchronization-based computational analysis and may have signaling effects. Spatially dispersed K+ release would have little effect on extracellular K+ concentration and allow K+ accumulation by the less powerful neuronal Na+,K+-ATPase, which is not stimulated by increases in extracellular K+. Since the Na+,K+-ATPase exchanges 3 Na+ with 2 K+, it creates extracellular hypertonicity and cell shrinkage. Hypertonicity also stimulates NKCC1, which, aided by -adrenergic stimulation of the Na+,K+-ATPase, causes regulatory volume increase, furosemide-inhibited undershoot in [K+]e and perhaps facilitation of the termination of slow neuronal hyperpolarization (sAHP), with behavioral consequences. The ion transport processes involved minimize ionic disequilibria caused by the asymmetric Na+,K+-ATPase fluxes.